The Approach to Develop Arabic Learning for General Speaker: a Synthesis from Arabic Learning Handbook for Ordinary People - Wisatrat, Wilailak; Naknawa , Dulyawit (Journal of Letters, 2023)
This research explores, analyzes, and proposes an approach to develop an Arabic language learning manual for the general public, applying a qualitative method by selecting purposive sampling data from 17 Arabic learning manuals from the public book market. Results showed that Arabic language learning manuals can be divided into three main types: (1) grammar manuals (2) vocabulary manuals and (3) conversation manuals. However, each type of manual has different problems. The main problem with all types is a lack of proofreading, resulting in typing errors. Therefore, the main approach to develop an Arabic learning manual is to refine manuscripts and conduct a more intensive academic review.